2020
DOI: 10.34067/kid.0002802020
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of Oral for Intravenous Cyclophosphamide in Membranous Nephropathy

Abstract: BackgroundOptimal immunosuppressive treatment for membranous nephropathy is still a matter of controversy. Current recommendations include oral cyclophosphamide combined with steroids (modified Ponticelli regimen) as first-line treatment in patients who are high risk. However, concerns about the cumulative toxicity of oral cyclophosphamide persist. In the last 30 years, a protocol based on low-dose intravenous cyclophosphamide plus steroids has been used to treat membranous nephropathy in Uruguay. We aimed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…A retrospective analysis of 32 cases with PMN treated with intravenous CTX (500–750 mg/m2 every month for 6 months) plus steroids reported that 81% of the patients achieved clinical remission [ 25 ]. A long-term observational study of 55 PMN patients found that 70.9% of patients achieved clinical response with CTX regimen [ 26 ]. Another retrospective analysis studied 40 patients treated with intravenous CTX (600 mg/m2 every 4 weeks for up to 6 months) plus steroids.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective analysis of 32 cases with PMN treated with intravenous CTX (500–750 mg/m2 every month for 6 months) plus steroids reported that 81% of the patients achieved clinical remission [ 25 ]. A long-term observational study of 55 PMN patients found that 70.9% of patients achieved clinical response with CTX regimen [ 26 ]. Another retrospective analysis studied 40 patients treated with intravenous CTX (600 mg/m2 every 4 weeks for up to 6 months) plus steroids.…”
Section: Discussionmentioning
confidence: 99%
“…The cyclophosphamide dose used to treat the breast cancer was a lower dose than that used to successfully treat primary MN; however the contribution of this treatment to the resolution of her nephrosis cannot be completely excluded, indeed there are reports of partial remission of MN with Cyclophosphamide doses of less than 3 g [ 4 ]. Although less likely given her high PLA2R titre, a spontaneous remission of primary MN is also possible independent of the malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…The TR rate of immunosuppressive therapy reported by different studies is inconsistent. To estimate the pooled TR rate of the control group, we conducted fixed-effects meta-analyses among data from five studies [ 20 24 ] by using the R software (version 4.0.2) plugin metaprop function. After calculation, the pooled TR rate of cyclical CTX/steroids regime is 56%(95%CI, 50.7–61.4) with a low heterogeneity (I 2 = 0.000%, P < 0.000).…”
Section: Interventionsmentioning
confidence: 99%